2003
DOI: 10.1002/crat.200310125
|View full text |Cite
|
Sign up to set email alerts
|

Optical and microhardness studies of semiorganic nonlinear optical material: L‐ histidine tetrafluoroborate

Abstract: L-histidine tetrafluoroborate (L-HFB) a semiorganic nonlinear optical material has been synthesized in aqueous solution at 50ºC and characterized by FT-IR and FT-Raman spectroscopy studies. The solubility was determined in different solvents such as water, methanol and water mixture of methanol. The single crystals with dimensions 15x12x3 mm 3 were grown by slow evaporation method within four weeks with approximate growth rate of 0.25 mm/day. The grown crystals have been subjected to single crystal X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 11 publications
1
13
0
Order By: Relevance
“…It has SHG efficiency five times greater than KDP [5]. The FT-IR, FT-Raman and optical studies of this material have already been reported by our group [6]. In the present investigations the growth aspects of LHFB in two different pH (3.14 & 2.74) values have been studied.…”
Section: Introductionmentioning
confidence: 79%
“…It has SHG efficiency five times greater than KDP [5]. The FT-IR, FT-Raman and optical studies of this material have already been reported by our group [6]. In the present investigations the growth aspects of LHFB in two different pH (3.14 & 2.74) values have been studied.…”
Section: Introductionmentioning
confidence: 79%
“…In recent years, there has been considerable interest on organic materials due to their potential applications such as frequency conversion, optical signal processing, light modulation, optical switching and logic gates [1][2][3] . Semi-organic crystals are suitable for highly aligned and stable orientation of NLO chromophores in the crystal lattice 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Metal ion doped materials are currently receiving a great deal of attention due to the rapid development of laser diodes [10][11]. Meantime several foreign metallic cations existing in the parent compounds with high valancy and small radii, such as Ni 2+ , Co 2+ will affect the whole growth process and enhances physical properties.…”
Section: Introductionmentioning
confidence: 99%